LANGUAGE APTITUDE AND ITS RELATION TO ENGLISH SECOND LANGUAGE LEARNERS' MASTERY OF GRAMMATICAL RULES: a case study of english conditional sentences - Nurdini, - (2014)
This research paper attempts to reveal the correlation of language aptitude and English second language learners' mastery of conditional sentences. It also investigates the relationship between three constituent abilities of language aptitude, such as Rote Memory, Phonetic Coding, and Grammatical Sensitivity, and the learners' mastery of conditional sentences. The study employed a quantitative method. The theory used in the study is language aptitude which is proposed by John Carroll (1981). Two instruments were used in the study, such as the Modern Language Aptitude Test and test on conditional sentences, while the subject of the study involved 20 students who are taking English Language and Literature as their major in a state university in Bandung. The findings reveal that there is a weak positive relationship between language aptitude and English second language learners' mastery of conditional sentences (r = 0.35). The three constituent abilities of language aptitude also correlate to English second language learners' mastery of conditional sentences. The obtained r of Rote Memory is -0.39 which indicates a weak negative relationship, while the obtained r of Phonetic Coding is -0.01 and Grammatical Sensitivity is 0.73.